Pendekatan Konseling Berbasis Client Centered Ditinjau dari Yohanes 4:4-40 Bagi Penanganan Kasus Generalized Anxiety Disorder dan Insecure Parents Attachment Pada Remaja - Linawati Linawati; Thomson Siallagan; Rika Kartika; Bahagia Tarigan (Jurnal Teologi Cultivation, 2021)
Abstract:Cases of counseling for adolescents with a background of Generalized Anxiety Disorder (GAD) and Insecure Parents Attachment (IPA) problems are increasing at this time. The purpose of this study are improving the counseling skills of counselors though a Client Centered-based counseling approach in counseling adolescents with anxiety and insecure conditions to achieve the success of the first meeting session and also the success of the long-term counseling process on GAD IPA, as well as make adolescents grow and become more similar to the picture. The Son of God (Rom. 8:29) fits the purpose of Christian counseling. The story of John 4:4-40 illustrates the Client Centered approach, in the process of Jesus' dialogue with the Samaritan woman, a woman who was in anxiety and inseruce taking water during the day. There is a non-judgmental dialogue process, namely unconditional positive regard - acceptance and unconditional love; and congruent -trustworthy and safe, forming the necessary conditions in the therapeutic process. The method used is field qualitative (case study). The technique of collecting data is through semi-structured interviews, both informal and formal.  In this study, it can be concluded that the strategy to build the right starting skills (spirit listening, empathy, understanding, and acceptance) for teenagers is very important in the first session. Activities for parents in the form of psychoeducation, parenting sessions, periodic evaluations, and referrals for family counseling are efforts that can support the success of the long-term counseling process for adolescents. Through the experience of a therapeutic relationship (reconnecting – reattachment) in holistic counseling, that it shown by the counselor with an open, sincere, warm personal attitude, non-possessive acceptance, and empathy, it will bring new experiences for teenagers to be fully accepted and it is hoped that through the work of the Holy Spirit personally, teenagers can grow to be more like the image of the Son of God, the Lord Jesus Christ. Keywords: client centered, generalized anxiety disorder, insecure parents attachment Abstrak:Kasus konseling pada remaja dengan latar belakang masalah Generalized Anxiety Disorder (GAD) dan Insecure Parents Attachment (IPA) semakin meningkat pada saat ini. Tujuan penelitian ini adalah meningkatan keterampilan konseling para konselor melalui pendekatan konseling berbasis Client Centered yang sesuai pada konseling remaja dengan kondisi anxiety dan insecure untuk mencapai keberhasilan sesi pertemuan pertama dan juga keberhasilan pada proses konseling jangka panjang pada GAD IPA, serta membuat klien remaja bertumbuh dan menjadi semakin serupa dengan gambar Anak Allah (Rm.8:29) sesuai dengan tujuan konseling Kristen. Kisah Yohanes 4:4-40 memberikan gambaran pendekatan Client Centered, dalam proses dialog Yesus dengan perempuan Samaria, seorang yang sedang dalam kecemasan dan inseruce mengambil air disiang hari. Terjadi proses dialog yang non-judgemental, yaitu unconditional positive regard -pemerimaan dan kasih tak bersyarat; dan congruent -dapat dipercaya dan aman, membentuk kondisi-kondisi yang diperlukan dalam proses terapeutik Metode yang digunakan adalah kualitatif lapangan (studi kasus). Teknik pengumpulan data melalui wawancara semi terstuktur baik informal maupun formal.  Dalam penelitian ini dapat disimpulkan bahwa stategi membangun starting skill yang tepat (spirit listening, empathy, understanding, dan acceptance) bagi remaja sangat penting di sesi pertama. Kegiatan bagi orang tua berupa psikoeduasi, sesi parenting, evaluasi berkala dan rujukan untuk konseling keluarga merupakan upaya yang dapat mendukung keberhasilan proses konseling jangka panjang pada remaja. Melalui pengalaman hubungan terapeutik yang ditunjukan konselor dengan sikap pribadi yang terbuka, tulus, hangat, penerimaan yang nonposesif, dan empati yang membentuk kondisi-kondisi yang diperlukan dalam proses terapeutik (reconnecting–reattachment) akan membawa pengalaman baru bagi remaja diterima seutuhnya dan diharapkan melalui karya Roh Kudus secara pribadi remaja dapat bertumbuh menjadi semakin serupa dengan gambar Anak Allah Tuhan Yesus Kristus sesuai dengan tujuan konseling Kristen. Kata kunci: client centered, generalized anxiety disorder, insecure parents attachment